PCR-based molecular markers for identification of taxa from the Calypogeia fissa complex (Jungermanniopsida, Calypogeiaceae) - Buczkowska, Katarzyna; Gonera, Patrycja; Hornik, Bartosz (Biodiversity: Research and Conservation, 2013)
Within Calypogeia fissa, two subspecies connected with geographic distribution are formally recognized: C. fissa subsp.fissa in Europe and C. fissa subsp.neogea in North America. Isoenzyme studies have shown that the European subspecies is genetically differentiated and composed of three genetically distinct groups PS, PB and G. The PS group has the most distinctive morphological features, but no morphological diagnostic traits have been found for groups PB and G. The sequence characterized amplified region (SCAR) markers developed on the basis of ISSR markers, applied in the study, allowed the delimitation of all groups distinguished in Europe within the C. fissa complex (PS, PB and G). The markers also revealed genetic differences between the European and American subspecies. Five primer pairs (Cal01, Cal03-Cal06) of the six pairs studied are useful as the diagnostic tool for the identification of particular groups from the C.fissa complex. The examined SCAR markers showed that the PS group of C.fissa subsp.fissa was the most distinct; it differed from both groups PB and G as well as from C.fissa subsp.neogea. All plants determined on the basis of diagnostic isozyme loci as the PS group amplified a longer product (380 bp) of the Cal04 primer pair than the rest of studied groups and yielded no amplification products in Cal03, Cal05 and Cal06 primers. The primer pair Cal03 distinguished the plants of the PB group from the remaining groups, since only the PB group generated a PCR product of about 290 bp. The genetic differences between all four studied groups of the C.fissa complex were supported by DNA sequences of the SCAR marker Cal04.